LACUNAS AND NON-EQUIVALENT LEXICS AS A REFLECTION OF LINGUISTIC CULTURE - Jumamuratovа R. (The journal of contemporary issues in business and government, 2021)
This article deals with linguistic gaps and the correlation of non-equivalent vocabulary with them in the English and Karakalpak languages. Invisible from within, but revealed when comparing two linguocultures, lacunas and non-equivalent vocabulary are fixators of their specificity and in the teaching process deserve special attention, since they also carry rich information about the culture of the language being studied and the mentality of its bearer.